Education, Development and Knowledge: New Forms of Unequal Change under Globalization. The Case of Sub Saharan Africa Countries - Chagas Lopes, Margarida (Journal of Research in Educational Sciences; Vol 2 No 2 (2011): JRES, Volume II, Issue 2(4), Winter 2011, 2011)
One of the leading mismatches brought about by globalization has to do with the severe opposition between the national frameworks in which qualifications and skills are being developed and the wider international contexts in which they are increasingly utilized and reproduced. This gulf becomes almost impossible to overcome and imposes a growing inequality in the access to knowledge in the global economy as the prevalent forms of economic regulation are rendered obsolete. The limitations displayed by national systems of education and training interact with the growing insufficiencies in the performance of labor market and innovation hetero regulators. As a result, increasing flows of excluded workers have been paving the ways between the new global development centers and the emerging new peripheries.